The effects of alveolar bone loss and miniscrew position on initial tooth displacement during intrusion of the maxillary anterior teeth: Finite element analysis - Cho, Sun-Mi; Choi, Sung-Hwan; Sung, Sang-Jin; Yu, Hyung-Seog; Hwang, Chung-Ju (Korean journal of orthodontics (2012), 2016)
The aim of this study was to determine the optimal loading conditions for pure intrusion of the six maxillary anterior teeth with miniscrews according to alveolar bone loss. A three-dimensional finite element model was created for a segment of the six anterior teeth, and the positions of the miniscrews and hooks were varied after setting the alveolar bone loss to 0, 2, or 4 mm. Under 100 g of intrusive force, initial displacement of the individual teeth in three directions and the degree of labial tilting were measured. The degree of labial tilting increased with reduced alveolar bone height under the same load. When a miniscrew was inserted between the two central incisors, the amounts of medial-lateral and anterior-posterior displacement of the central incisor were significantly greater than in the other conditions. When the miniscrews were inserted distally to the canines and an intrusion force was applied distal to the lateral incisors, the degree of labial tilting and the amounts of displacement of the six anterior teeth were the lowest, and the maximum von Mises stress was distributed evenly across all the teeth, regardless of the bone loss. Initial tooth displacement similar to pure intrusion of the six maxillary anterior teeth was induced when miniscrews were inserted distal to the maxillary canines and an intrusion force was applied distal to the lateral incisors. In this condition, the maximum von Mises stresses were relatively evenly distributed across all the teeth, regardless of the bone loss.